ASPEK YURIDIS PEMBUBARAN BADAN USAHA BANK KARENA MELANGGAR HUKUM MENURUT UNDANG – UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS MELALUI MEKANISME PERMOHONAN PEMBUBARAN PERSEROAN TERBATAS KEPADA PENGADILAN NEGERI - Fitriani, Agnes; Sari, Desi Puspita; Purwati, Siti Ayu Resa; Lestari, Neng Aini Sri Sunda; Tusyadiah, Hafipah; Siswajanthy, Farahdinny (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The research examines the Legal Analysis on the Dissolution of a Bank Business Entity (PT) through a petition filed by the District Attorney based on Law Number 40 of 2007 regarding Limited Liability Companies and Law Number 10 of 1998 concerning Banking. The methodology employed in this study is legal research, specifically juridical-normative with a reliance on library study data. Both primary and secondary data were utilized, with data processing conducted through library research. The dissolution of a Bank Business Entity (PT) may be executed by the state through the District Attorney's Office. Such dissolution can occur if the entity violates legal provisions and adversely impacts society and the state. According to regulations set by the Attorney General, a request for dissolution can be made if the PT, through its management structures, is proven to have violated legal provisions that entail criminal penalties. Furthermore, a PT may be dissolved if it breaches legal provisions that lack criminal penalties. Bank Business Entities structured as PTs must adhere to the stipulations of Law Number 40 of 2007, with criteria for violations containing criminal sanctions outlined in Law Number 10 of 1998 concerning Banking